2023
DOI: 10.3390/jpm13010139
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Accuracy of Two Different Dynamic Navigation System Registration Methods for Dental Implant Placement in the Posterior Area: An In Vitro Study

Abstract: Purpose: To compare the U-tube and cusp dynamic navigation system registration methods in the use of dental implant placement, and to assess the influence of the location of missing teeth on these registrations. Methods: 32 resin mandible models and 64 implants were utilized, with implants being placed using one of the two registration methods selected at random. Accuracy was measured through the superimposition of the final and planned implant positions. Angular deviation, 3D entry deviation, and 3D apex devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This may be because both of these de- be a consequence of insufficient sample size. Wei et al observed significant differences with respect to apex and entry deviation for cases with and without distal extension when examining the effect of the edentulous area while working with a U-shaped tube device, with greater accuracy in the latter group (Wei et al, 2023). Based on these results, placing the U-shaped tube on the side opposite the dentition may be warranted when the implant site is in an area with an absence of distal extension.…”
Section: Ta B L Ementioning
confidence: 99%
“…This may be because both of these de- be a consequence of insufficient sample size. Wei et al observed significant differences with respect to apex and entry deviation for cases with and without distal extension when examining the effect of the edentulous area while working with a U-shaped tube device, with greater accuracy in the latter group (Wei et al, 2023). Based on these results, placing the U-shaped tube on the side opposite the dentition may be warranted when the implant site is in an area with an absence of distal extension.…”
Section: Ta B L Ementioning
confidence: 99%